Greenland, view of Kjerulf Fjord annotated by Louise A. Boyd - Boyd, Louise Arner, 1887-1972 (1931)
August 1, 1931. Kjerulfs [Kjerulf] Fjord. Extreme inner end. Junction of streams of Right and Left Valley. In background (extreme left) is sloping side of innermost southern point of mountain range forming the eastern side of Kjerulfs [Kjerulf] Fjord, from its entrance at Kaiser Franz Josef Fjord [Kejser Franz Joseph Fjord] to the point where it forms the eastern side (left side looking up) of Left Valley and in this photo it is seen curving E.N.E. to disappear around to the left and (beyond here) forms the north side of Dickson [Dicksons] Fjord. In background, L.A. B.'s Scoop Mt. [Mountain] and the range of mts [mountains] which here form the eastern side of Hisinger Glacier [Hisinger Gletscher]. This is the northern most point of this range. To the left the range runs to the East and forms the south side of Dickson [Dicksons] Fjord. Background shows stream of Left Valley; foreground stream of Right Valley. Note: Is low peak at base of mountains (in line with stream) the same peak or nanatak in photos 26-H-18 and 24-F-5?